Analisis Pengaruh Oversize 100 Terhadap Performa Mesin Sepeda Motor 4 Tak Sohc 150 - Awal Saputra; Mulyadi; Heppi Familiana (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
Motorcycles are a versatile means of transportation that are growing as well the development is very fast. Almost all parts of the system on technology automotive, both motorcycles and cars can change the piston size from the standard size becomes larger which is called the oversize process. Research object using a 150cc SOHC motor. This study aims to determine influence motor performance and compare it with standard pistons as well determine the impact of fuel consumption after the oversize process is carried out with a 63.5 mm piston changed to 64.5 mm, with a maximum power of 9.57 hp at 6600 rpm to 10.24 hp at 6600 rpm. Next round torque from 10.55 Nm to 11.67 Nm after being oversized. From the results show that by oversizing the piston there is an increase in stroke volume, however the pressure in the combustion chamber decreases, the compression ratio increases. As for power and style, it is relatively the same as a standard size motorbike, as well slight increase in fuel consumption.